Evolution and complexity in economics revisited - Kurt Dopfer (Max Planck Institute of Economics, 2011)
The paper discusses recent trends in the sister sciences of evolutionary economics and complexity economics. It suggests that a unifying approach that marries the two strands is needed when reconstructing economics as a science capable of tackling the two key questions of the discipline: complex economic structure and evolutionary economic change. Physics, biology and the cultural sciences are investigated in terms of their usefulness as both paradigmatic orientation and as toolbox. The micro-meso-macro architecture delineated puts meso centre stage, highlighting its significance as structure component and as process component alike, thereby allowing us to handle the key issues of structure and change.
urn:nbn:de:gbv:27-20110630-113058-2
Keywords: 330; Evolutionsökonomik; Komplexe Systeme; Wirtschaftswissenschaft; Theorie